2011
DOI: 10.1512/iumj.2011.60.4339
|View full text |Cite
|
Sign up to set email alerts
|

Variational equivalence between Ginzburg-Landau, XY spin systems and screw dislocations energies

Abstract: We introduce and discuss discrete two-dimensional models for XY spin systems and screw dislocations in crystals. We prove that, as the lattice spacing ε tends to zero, the relevant energies in these models behave like a free energy in the complex Ginzburg-Landau theory of superconductivity, justifying in a rigorous mathematical language the analogies between screw dislocations in crystals and vortices in superconductors. To this purpose, we introduce a notion of asymptotic variational equivalence between famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
96
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(99 citation statements)
references
References 29 publications
3
96
0
Order By: Relevance
“…Secondly, we wanted to push the methods developed for nonlocal energies beyond the case of radially symmetric potentials, still retaining the critical, logarithmic singularity at zero. Finally, we wanted to explore the connection between the theory of vortices and the theory of dislocations, which has been successfully exploited so far in the case of discrete and screw dislocations (see, e.g., [1,2]). The literature on nonlocal interaction energies is vast.…”
Section: )mentioning
confidence: 99%
“…Secondly, we wanted to push the methods developed for nonlocal energies beyond the case of radially symmetric potentials, still retaining the critical, logarithmic singularity at zero. Finally, we wanted to explore the connection between the theory of vortices and the theory of dislocations, which has been successfully exploited so far in the case of discrete and screw dislocations (see, e.g., [1,2]). The literature on nonlocal interaction energies is vast.…”
Section: )mentioning
confidence: 99%
“…In [18], it has been proved that the screw dislocations functionals 4π 2 SDε | log ε| Γ-converge to π|µ|(Ω), where µ is the limiting vorticity measure and is given by a finite sum of Dirac masses. In [2], it has been shown that the energies SDε | log ε| h and GLε | log ε| h (with h ≥ 1) are variationally equivalent, which means, roughly speaking, that they have the same Γ-limit (up to a factor) and share the same equicoerciveness property with respect to the same convergence. The Γ-limit |µ|(Ω) is not affected by the position of the singularities and hence does not account for their interaction, which is an essential ingredient in order to study the dynamics.…”
Section: Overview Of the Model For Discrete Screw Dislocationsmentioning
confidence: 99%
“…A linear-elastic model of a finite number of wellseparated dislocations with a core-radius regularization was studied by De Luca et al [22] and extended by Scardia and Zepperi [58] to nonlinear elasticity with subquadratic growth. The relation of the model to Ginzburg-Landau and spin models was discussed by Alicandro et al [3]. Second-order expansions of the energy were employed by Leoni and Cermelli [17] to derive leading-order approximations of the interaction energies.…”
Section: Introductionmentioning
confidence: 99%